The effects of brief emotional acceptance instructions on emotional distress and compulsive urges of various obsessive-compulsive symptoms dimensions - Cassandra C. H. See; Vanessa S. Y. Tan; Jia Min Tan; Oliver Sündermann (Journal of Experimental Psychopathology, 2023)
Background and Objectives: Emotion regulation (ER) deficits are increasingly implicated in obsessive-compulsive symptoms (OCS). The ER difficulty of ‘non-acceptance of emotions’ has been most consistently found to correlate with OCS – albeit not uniformly with all OCS dimensions. This study examined the causal relationships between the acceptance of emotions and four OCS dimensions: contamination, responsibility of harm, unacceptable thoughts and symmetry. Methods: Participants in this online study rated their baseline emotional distress and compulsive urges to OC scenarios corresponding to each OCS dimension. After completing questionnaires on ER, OCS, anxiety and depressive symptoms, participants were randomly assigned to two conditions and instructed to observe and accept their emotions (acceptance condition; n = 180) or observe their emotions (control condition; n = 185) as they re-read the scenarios. Participants then rated their post-manipulation emotional distress and compulsive urges to each scenario. Results: The instructions to accept emotions resulted in lower compulsive urges to the responsibility of harm scenario, for participants with lower baseline compulsive urges. There were no other group differences on post-manipulation measures. Conclusions: The current findings suggest that even brief instructions to accept one’s emotions reduced compulsive urges, pointing to the potential clinical utility of enhancing the acceptance of emotions.